Basal and cold-induced fatty acid uptake of human brown adipose tissue is impaired in obesity - Saari TJ; Raiko J; U-Din M; Niemi T; Taittonen M; Laine J; Savisto N; Haaparanta-Solin M; Nuutila P; Virtanen KA. (Nature Research, 2022)
atty acids (FA) are important substrates for brown adipose tissue (BAT) metabolism, however, it remains unclear whether there exists a difference in FA metabolism of BAT between lean and obese healthy humans. In this study we evaluated supraclavicular BAT fatty acid uptake (FAU) along with blood perfusion in lean and obese subjects during cold exposure and at room temperature using positron emission tomography (PET)/computed tomography (CT). Additionally, tissue samples were taken from supraclavicular region (typical BAT region) from a subset of subjects to evaluate histological presence of BAT. Non-shivering cold stress elevated FAU and perfusion of BAT in lean, but not in obese subjects. Lean subjects had greater FAU in BAT compared to obese subjects during cold exposure and interestingly also at room temperature. The higher BAT FAU was related to younger age and several indicators of superior systemic metabolic health. The subjects who manifested BAT histologically had several folds higher BAT FAU compared to subjects with no such histological manifestation. Together, obese subjects have less active tissue in supraclavicular region both in basal and cold-activated state and the FA metabolism of BAT is blunted in obesity.